SYED MUHAMMAD NAQUIB AL-ATTAS’ CRITICS TOWARD SECULARISM - Nabila Huringiin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
The issue of modernity that is crucial today is the development of secularism in various fields. One of the main things to highlight is the popularity of secularism, which has a worldview that is contrary to Muslims. It was Syed Muhammad Naquib Al-Attas who was the most vocal in voicing his criticism and proposing the solutions he offered in the form of the concept of Islamization of Present Day Knowledge. The research method used by the author is descriptive analysis in analyzing the views of Syed Muhammad Naquib Al-Attas on Secularism. And the author uses the philosophical approach for this research. There are many confusions in Secularism thought, one of which is the opinion about the separation of Secularization and Secularism which in the end will also lead to Secularizationism. And the Islamization of contemporary Science is the most vocal form of Al-Attas' criticism of Secularism. Because with Islamization, the elements of secular Western culture, spirit, character, and personality contained in science can be cleaned.